Gender disparity in living organ donation: a qualitative analysis of experiences and perceptions of female donors in Pakistan - Muhammad Ishaq; Javeria Saleem; Ruhma Binte Shahzad; Mahrukh Iqbal; Abida Tehreem; Raja Sajjad Asghar; Aleena Touqeer; Gul Mehar Javaid Bukkhari (BMJ Open)
Objectives This study aims to explore and analyse the interplay of sociocultural, psychological and institutional factors, gender roles and power dynamics in shaping the decision-making processes and experiences of living kidney and liver donors in Punjab, specifically focusing on women.Design This study employed a qualitative approach, using in-depth interviews to delve into the narratives and experiences of living kidney and liver donors in Punjab.Setting Punjab Human Organ Transplantation Authority (PHOTA), Lahore, Punjab, Pakistan.Participants 17 participants registered at the PHOTA for kidney or liver donation.Results Interviews with living donors at PHOTA, Lahore, provided qualitative data, which was then systematically coded and analysed to identify recurring themes that explore the underlying social and cultural reasons for the observed gender disparity. The qualitative research yielded 17 interviews to include in the analysis, representing the voices of living kidney and liver donors. The study resulted in the following themes emerging: (1) female donation as a consequence of economic vulnerability; (2) comorbidities impacting donor eligibility; (3) altruism among female donors; (4) social and self-benefit of the donors and (5) social obligation on the female donors. These themes transcended the medical considerations and highlighted the interplay between social norms, family dynamics and gendered expectations surrounding caregiving and self-sacrifice.Conclusion The findings of this study underscore the significant relationship between gender roles, economic pressures and social expectations in the context of living organ donation. The study’s results highlight the urgent need for targeted interventions to address the gender gap in living kidney and liver donation. By acknowledging the influence of social and economic factors, strategies to create a more equitable landscape for living kidney and liver donors can be created.